Numerical Study of Gas Separation of Pressure-Driven Binary Mixture Flows Through a Microchannel (Communications in Computational Physics, 2025)
The gas separation phenomenon of the pressure-driven binary mixture (helium–argon) flows in a microchannel is investigated numerically over a wide rangeof Knudsen numbers using the discrete unified gas kinetic scheme. The effects of inlet/outlet pressure ratio and Knudsen number on gas separation are studied numerically. It is found that the separation is strengthened with the increase of pressureratio, and exhibits different trends under different rarefied conditions. The degree ofgas separation changes nonlinearly with the outlet Knudsen number and exhibits amaximum in the transitional regime. In particular, we find that the relative pressuredeviation and the velocity ratio between light species helium and heavy species argoncan be served as indicators for gas separation under different working conditions. Finally, the phenomenon of Knudsen minimum is observed for the light species and gasmixture in the transition regime, but it does not appear for the heavy species withinthe considered Knudsen number range (≤10).
Keywords: Gas separation; discrete unified gas kinetic scheme; pressure-driven flow; microchannel.